Menumbuhkan Jiwa Entrepreneurship Bagi Gen Z - Eko Fikriando; Desmawati Roza; Aulia Fikrina (Universitas 45 Surabaya, 2024)
Competition for workers in the era of globalisation is getting tighter, this condition requires improving the quality of human resources to be able to compete, but in reality, the competitiveness of Indonesian workers is still low, as evidenced by the high number of workers who are not absorbed in the world of business and industry, which results in high unemployment in Indonesia. One of the causes of increasing unemployment cannot be separated from the implementation of an education system that still only emphasizes theory rather than practice. Therefore, it is important to improve the identity of prospective high school graduates who have high-quality human resources, and skills and can compete, for example through education in Entrepreneurship and Digital Marketing lessons. Entrepreneurship skills are an ability that a person has as a form of assigning knowledge and applying it to real activities in his life. Efforts to realize this goal at the high school level have been developed and implemented in entrepreneurship subjects in the national curriculum for the vocational secondary level. It is important to provide an understanding of entrepreneurship to students, especially high school students so that they are more aware of the business world and ready to be part of the entrepreneurial development process.